The desert bride [videorecording (DVD)] - Atán, Cecilia; Atán, Cecilia; Pivato, Valeria; Pivato, Valeria; García, Paulina; Rissi, Claudio (Strand Releasing Home Video, 2018)
A middle-aged woman who has worked for decades as domestic live-in help with a Buenos Aires family, has to find a new place to live when the family decides to sell the house.